County-Level Unemployment Rates and Service Intensity in Primary Care Physician Offices for Medicare Patients. (June 2021) - Li, Jing; Chen, Alice; Parks, Moon; Ghosh, Arnab; Casalino, Lawrence P.
The macroeconomic environment has been shown to affect health-care service utilization. We examined the relationship between unemployment rate and service intensity among a nationally representative sample of primary care office visits from Medicare patients by merging data from the 2006–2012 National Ambulatory Medical Care Survey with unemployment data from the Bureau of Labor Statistics. Multispecialty practices demonstrated increases in the number of electrocardiogram tests prescribed and the number of return appointments scheduled. In contrast, single-specialty practices did not respond on those margins and instead increased the likelihood of administering diagnostic and screening examinations. We found no significant relationship between unemployment rates and the number of laboratory and imaging services, magnetic resonance imaging use, referrals, or medication prescribing. These results were robust to controlling for extensive visit characteristics and county-, year-, and month-fixed effects. Our results suggest that physicians responded to the Great Recession by changing their practice behavior.